2019
DOI: 10.1186/s13063-019-3418-0
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment strategies for predominantly low-income, multi-racial/ethnic children and parents to 3-year community-based intervention trials: Childhood Obesity Prevention and Treatment Research (COPTR) Consortium

Abstract: Background The recruitment of participants into community-based randomized controlled trials studying childhood obesity is often challenging, especially from low-income racial/ethnical minorities and when long-term participant commitments are required. This paper describes strategies used to recruit and enroll predominately low-income racial/ethnic minority parents and children into the Childhood Obesity Prevention and Treatment Research (COPTR) consortium. Methods The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(67 citation statements)
references
References 27 publications
2
65
0
Order By: Relevance
“…Communications informing the target population about the purpose and processes of the research helps foster trust and encourage participation ( 48 50 ). Messaging about the study during enrollment should emphasize benefits in easy to understand language and explain procedures like randomization ( 41 , 46 ). For example, community CAB members identified that intervention benefits were obscured under technical consent procedures and that predetermined intervention preferences and mistrust of randomization processes were causing dissatisfaction and potentially influencing early dropout.…”
Section: Discussionmentioning
confidence: 99%
“…Communications informing the target population about the purpose and processes of the research helps foster trust and encourage participation ( 48 50 ). Messaging about the study during enrollment should emphasize benefits in easy to understand language and explain procedures like randomization ( 41 , 46 ). For example, community CAB members identified that intervention benefits were obscured under technical consent procedures and that predetermined intervention preferences and mistrust of randomization processes were causing dissatisfaction and potentially influencing early dropout.…”
Section: Discussionmentioning
confidence: 99%
“…Knowing that the program attracts more children and retains more children in the 10-12 year old age range, a more focused effort regarding advertising and teaching delivery will be directed at this specific age group. 10 Although the posttest group showed an average improvement in nutrition knowledge over the pretest group, this finding may be inconsequential since posttest groups only improved by 0.6 of a question overall. Hereafter, participants will be randomly assigned numbers to track individual development from pretest surveys to posttest surveys.…”
Section: Discussionmentioning
confidence: 91%
“…This data can also bolster understanding of retention rates to determine if location, demographics, or participation in other programs from a trusted organization impacts retention. 10 The program averaged a retention rate of 50% from week one to week four. In the future, the program will explore if vacation and travel impacts participation in programs hosted over the summer.…”
Section: Discussionmentioning
confidence: 99%
“…But, clinical trials for addressing medical conditions (e.g. coronary heart disease, obesity) have successfully recruited participants at the practice, provider, and patient levels in primary care settings [ [14] , [15] , [16] , [17] ]. The successful strategies at the practice and provider levels included academic detailing, peer recruitment, leveraging professional associations, conducting pilot studies, and engaging communities of interest [ 11 , 13 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%